Factors influencing contraceptive utilisation among postpartum adolescent mothers: a cross sectional study at China-Uganda friendship hospital - Rogers Wambi; Huzaima Mujuzi; Aggrey Siya; Changulo Maryhilda C; Ivan Ibanda; Nalubiri Doreen; Walimbwa Stanely (BMC, 2024)
Abstract Background Globally, modern contraceptives remain underutilized among postpartum mothers resulting in the rise of short birth intervals. While there are a range of other factors that moderate the uptake of contraceptive services, understanding the significance of their influence is critical in public health programming. This study sought to analyze maternal and health facility factors influencing the utilization of contraceptives among postpartum mothers in urban areas of Uganda. Methods Using a cross-sectional study design, a health facility-based study in urban areas of Kampala was conducted from January to March 2023. A total of 332 women aged between 15 and 22 years were randomly selected for the interviews using semi-structured questionnaires. The data was analyzed using a statistical software program R version 4.1.2. Chi-square and multivariable logistic regression were used to determine factors associated with postpartum contraceptive intake among adolescent mothers. Results Overall, 28.3% of contraceptive usage was reported in the current study. The majority of the respondents, 98 (29.52%), were within the age group of 17-18 years, and the unmarried were 255 (76.81%). Factors associated with contraception use were income below UgX 500,000 (OR 4.546; CI 1.785-12,193, p = 0.002), occupation status of housewife and student (OR: 3.526; CI: 1.452-8.812, p = 0.006), distance of less than 5 km from health facility (OR: 2.62; CI 1.97-3.55; p = 0.028), and having a contraceptive preference (OR: 3.526; CI: 1.452-8.812, p = 0.006). Conclusions Contraceptive use is low among adolescent post-partum mothers. Income, occupation status, proximity to a health facility, and preference for a particular contractive method are factors associated with contraceptive use in this study. Understanding attitudes and views regarding contraception use is therefore essential for creating effective interventions, given the detrimental effects of adolescent pregnancy.